Estudio De Percepción De Emprendedores Universitarios Sobre El Impacto De Un Programa Escolar De Emprendimiento En Sus Empresas, En Tehuipango, Veracruz - Mejía-Ochoa, Francisco Javier; Limón-Rivera, Rogelio; Rojas-Martínez, Juan Carlos; Peláez-Muñoz, Elyana Cristina; Hernández-Velásquez, Silvia; Fierro-Domínguez, Evaristo; Panzo-Macuixtle, Dulce María; Chipahua-Chipahua, Lorenzo; González-Pérez, Manuel (European Scientific Journal, ESJ, 2017)
Entrepreneurship has impacts on countries, generating jobs and socioeconomic development. In Mexico, from the 1980s, Higher Education Institutions develop entrepreneurship and self-employment promotion programs, to promote entrepreneurial philosophy among their students. In the State of Veracruz, since 2015 the Higher Technological Institute of Zongolica has developed the Social Entrepreneur and Self-Employment (SES) program. The objective of this research is to conduct a study of the perception of university entrepreneurs on the impact of the SES school program on their companies, in the municipality of Tehuipango, Veracruz. For which a questionnaire was designed, applied and validated to a population of 32 graduates of the entrepreneur program. It is concluded that the respondents agree with being entrepreneurs, consider having influenced socioeconomically in their municipality and perceive that the social entrepreneur and self-employment program influenced their level of entrepreneurship. Finally, it was identified the need to create a program of accompaniment to companies, as support so that they continue operating in the market.